2004
DOI: 10.1523/jneurosci.2982-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Dorsal Horn Calcium Channel α2δ-1 Subunit Upregulation Contributes to Peripheral Nerve Injury-Induced Tactile Allodynia

Abstract: Peripheral nerve injury induces upregulation of the calcium channel ␣ 2 ␦-1 structural subunit in dorsal root ganglia (DRG) and dorsal spinal cord of spinal nerve-ligated rats with neuropathic pain, suggesting a role of the calcium channel ␣ 2 ␦-1 subunit in central sensitization. To investigate whether spinal dorsal horn ␣ 2 ␦-1 subunit upregulation derives from increased DRG ␣ 2 ␦-1 subunit and plays a causal role in neuropathic pain development, we examined spinal dorsal horn ␣ 2 ␦-1 subunit expression with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
202
2
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(227 citation statements)
references
References 36 publications
(48 reference statements)
17
202
2
5
Order By: Relevance
“…The von Willebrand factor-A domain is involved in trafficking the VGCC a 2 d-1 subunit to the plasma membrane [23,65,66]. Knock-down of a 2 d-1 reduces pain hypersensitivity in an animal model of nerve injury [30]. It has also been confirmed that the antinociceptive and anti-allodynic effects of GBP and pregabalin are due to disruption of trafficking of the VGCC a 2 d-1 subunit to the presynaptic terminal membrane induced by nerve injury [25][26][27]32].…”
Section: Loss Of the Gabapentin Effect May Contribute To Gabapentinoimentioning
confidence: 92%
See 1 more Smart Citation
“…The von Willebrand factor-A domain is involved in trafficking the VGCC a 2 d-1 subunit to the plasma membrane [23,65,66]. Knock-down of a 2 d-1 reduces pain hypersensitivity in an animal model of nerve injury [30]. It has also been confirmed that the antinociceptive and anti-allodynic effects of GBP and pregabalin are due to disruption of trafficking of the VGCC a 2 d-1 subunit to the presynaptic terminal membrane induced by nerve injury [25][26][27]32].…”
Section: Loss Of the Gabapentin Effect May Contribute To Gabapentinoimentioning
confidence: 92%
“…Experimentally, expression of a 2 d-1, but not a 2 d-2 (another binding site of GBP), is significantly increased in both the dorsal root ganglia (DRG) and the dorsal horn of the spinal cord in animal models of peripheral neuropathic pain. This up-regulation is thought to contribute to the development of allodynia and hyperalgesia [28][29][30][31]. It has thus been proposed that gabapentinoids alleviate neuropathic pain by blocking the trafficking of a 2 d-1 to the presynaptic terminals of DRG neurons and this subsequently leads to reduced Ca 2?…”
Section: Introductionmentioning
confidence: 99%
“…A redução ou a falha da função desses receptores podem levar a hiperexcitabilidade neuronal do nervo lesado. Também, pode haver aumento das subunidades de canais de cálcio tipo α2δ no gânglio da raiz dorsal e na medula espinal 13 , fato que provoca a liberação de neurotransmissores excitatórios. A alteração fenotípica de fibras Aδ na dor neuropática causaria, de maneira semelhante, a liberação pré-sináptica de substância P facilitando a sensibilização do corno dorsal da medula espinal.…”
Section: Papel Da Sensibilização Centralunclassified
“…The reduction or failure of the function of those receptors can lead to neuronal hyperexcitability in the damaged nerve. Calcium channels α2δ subunits in the dorsal root ganglion and in the spinal cord can also be increased 13 , which cause the release of excitatory neurotransmitters. The phenotypic change of Aδ fibers in neuropathic pain would similarly cause the presynaptic release of substance P facilitating sensitization of the dorsal horn of the spinal cord.…”
Section: Pre-synaptic Changesmentioning
confidence: 99%
“…Cette surexpression des sous-unités α 2 δ 1 n'affecte ni l'expression de la sousunité α 1B , ni celle des sous-unités β [37]. L'injection intrathécale d'oligonucléotides antisens, visant à diminuer le niveau d'expression des sous-unités α 2 δ 1 , confère aux animaux un effet anti-allodynie [38]. De plus, l'injection intrathécale de gabapentine (un anticonvulsif et antiépileptique) (Tableau II), capable d'interagir in vitro avec les sous-unités α 2 δ, diminue également les douleurs allodyniques sur ces modèles animaux.…”
Section: Sous-unité a 2 Dunclassified